A numerical approach for crack-induced damage in tungsten carbide cutting tools during machining. (October 2021) - Bounif, K.; Abbadi, M.; Nouari, M.; Selvam, R.
Highlights: Numerical results showed that cracks deflect at the coating/substrate interface. Microscopic observations performed on a cutting tool confirm numerical predictions. High coating thickness results in reduction of crack initiation and propagation. Coating stiffness enhances crack initiation and propagation mechanisms. Large edge radius reduces the chance for crack initiation and propagation. Abstract: Cracking wear is one of the major phenomena that affect the lifetime of cutting tools. Delamination may be the last stage and the inevitable outcome of the propagation of cracks that may initiate anywhere in the coating or at the coating/substrate interface. To explore this phenomenon, the standard finite element analysis (FEA) FEM analysis was performed, in a first step, to calculate the energy necessary for crack deflection at the interface and penetration into the substrate. The numerical results showed that the cracks are more prone to deflect at the interface than penetrating into the substrate. This prediction was supported by microscopic observations. In a second step, a numerical model was developed based on the combination of the extended finite element method (XFEM) and the cohesive element method (CEM) formulations for different parameters in relation with machining performance improvements. The findings of the parametric study enabled to conclude that the low stiffness, large edge radius, large thickness and high rake angle of the coating protect the tool from cracking. In parallel, it was revealed that a substrate with lower rigidity results in the delay of the tool crack initiation.